Investment analysis and management - Bowyer, John W. (Homewood, Ill. : R. D. Irwin, 1972)
This edition has added more material on personal financial and investment management
Includes bibliographical references and index.
osc 06/09/2019
Loans
Keywords: Securities; Investment analysis; Investments